Wymagalna wierzytelność z autorskich praw majątkowych jako przedmiot egzekucji w postępowaniu cywilnym - Piesiewicz, Piotr Filip (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The subject of regulation in art. 18 of The Copyright Act is not only an enforcement of proprietary copyrights, but also an enforcement of a receivable due. However, this issue was not the subject of a broader discussion in the doctrine. In this text, the author points out that only such an approach to this issue gives the opportunity to fully understand and describe the institution of enforcement of receivable due. The research thesis thus forced to formulate a number of questions. First, the author answered the question, what can be the subject of enforcement from the point of view of art. 18 of the Copyright Act. Subsequently, he focused on the analysis of the provisions of the enforcement proceedings relating to enforcement of receivables. The analysis of execution against receivables required discussion of both basic stages of the proceedings, ie: attacht of the receivables (Articles 896-904 of Code of Civil Procedure) and a satisfaction of the creditor. In the second stage of the proceedings, the creditor may be satisfied by auction sale or a direct sale of receivables, or performance into the hands of the holder of the debtor.